Arabic Feminist Discourse: Insights from Wedding Invitation Cards in Jordan - Al-Abed Al-Haq, Fawwaz; Nuseir, Husam (Dirasat: Human and Social Sciences, 2022)
The present study examines through critical discourse analysis the practice of masking the bride’s name on Jordanian Muslim wedding invitation cards. Previous research has focused on the generic analysis structure of all components of wedding invitation cards, and masking the bride’s name was a minor matter in these studies. Most studies referred to the reason for this practice as either due to people’s religious (Islamic) beliefs or social norms. An electronic questionnaire was used to investigate Jordanian people’s attitudes toward this social practice. The questionnaire consisted of 23 self-report items, which targeted Muslim Jordanian males and females over 18. A total of 1646 Jordanian participants responded to the questionnaire. Furthermore, a sample of 400 Jordanian wedding invitation cards was collected from different districts that were used to compare the study data with the actual existence of the practice of masking the bride’s name. The sample covered the period between the beginning of September 2019 to February 2020. Our findings showed that masking the bride’s name was a prevailing practice within the Jordanian community and regional affiliation played a significant role in this practice. Gender played a significant role in the choices made by the participants. The practice of masking the bride’s name on wedding invitation cards was not related in any way to religious (Islamic) beliefs. Masking the bride’s name is a kind of discrimination and inequality between males and females in the Jordanian community.